Waves with finite amplitude in Bessel horns - ZAMORSKI, T. (Archives of Acoustics, 1990)
The equation of the propagation a one-dimensional wave with finite amplitude in Bessel horns filled with nondissipative fluid is formulated in this paper. The solution to the equation of the propagation is analysed with the small parameter method. It was proved that a sinusoidal wave with finite amplitude, generated on the entry of the waveguide, is deformed when it moves along the horn. This manifests itself with the generation of higher harmonics with amplitudes dependent on position and frequency. The case of a conical waveguide filled with air is considered on the basis of general formulae achieved for the family of Bessel horns. Particularily the second harmonic was taken into account.